Students' and Teachers' Perceptions of Bullying in High Schools - Syafriwana, Syafriwana (International Journal on Advanced Science, Education, and Religion, 2024)
This study aims to explore students' and teachers' perceptions of bullying in high schools and their responses to bullying cases. Using a qualitative approach with a case study method, the study involved 20 students and 10 teachers from two schools in city X, selected through purposive sampling. Data were collected through semi-structured interviews and focus group discussions (FGD), then analyzed using thematic analysis. The results indicate a difference in perceptions between students and teachers. Students tend to view verbal bullying as part of "normal" social interactions, whereas teachers consider bullying a serious issue that requires immediate intervention. Teachers are particularly concerned about physical and cyberbullying due to its significant impact on students' mental health. Both groups acknowledged the need for school policies and support to handle bullying cases effectively. These findings emphasize the importance of collaboration among students, teachers, and school administrators, as well as the need for anti-bullying educational programs and policies to create a safe and supportive environment for students.